Microalgae from Nordic collections demonstrate biostimulant effect by enhancing plant growth and photosynthetic performance - Chovanček Erik; Salazar João; Şirin Sema; Allahverdiyeva Yagut (WILEY, 2025)
We investigated the biostimulant potential of six microalgal species from Nordic collections extracted with two different procedures: thermal hydrolysis with a weak solution of sulfuric acid accompanied by ultrasonication and bead-milling with aqueous extraction followed by centrifugation. To this aim, we designed a phenotyping pipeline consisting of a root growth assay in the model plant Arabidopsis thaliana, complemented with greenhouse experiments to evaluate lettuce yield (Lactuca sativa L. cv. Finstar) and photosynthetic performance. The best-performing hydrolyzed extracts stimulated Arabidopsis root elongation by 8%-13% and lettuce yield by 12%-15%. The in situ measured photosynthetic performance of lettuce was upregulated in the efficient extracts: PSII quantum yield increased by 26%-34%, and thylakoid proton flux increase was in the range of 34%-60%. In contrast, aqueous extracts acquired by bead-milling showed high dependence on biomass concentration in the extract and an overall plant growth enhancement was not attained in any of the applied dosages. Our results indicate that hydrolysis of the biomass can be a decisive factor for rendering effective plant biostimulants from microalgae.